Cyclophosphamide promotes chronic inflammation-dependent immunosuppression and prevents antitumor response in melanoma - Sevko, Alexandra; Michels, Tillmann; Umansky, Ludmila; Ramacher, Marcel; Umansky, Viktor (The journal of investigative dermatology, 2013)
Low-dose cyclophosphamide (CP) therapy induces immunogenic tumor cell death and decreases regulatory T cell (Treg) numbers in mice with transplantable tumors. Using the ret transgenic murine melanoma model that resembles human melanoma, we detected no beneficial antitumor effects with such treatment, despite a decrease in Tregs. On the contrary, low-dose CP enhanced the production of chronic inflammatory mediators in melanoma lesions associated with increased accumulation of Gr1+CD11b+ myeloid-derived suppressor cells (MDSCs), which exhibit elevated suppressive activity and nitric oxide (NO) production as well as inhibition of T-cell proliferation. Moreover, the frequencies of CD8+ T cells in the tumors and their ability to produce perforin were decreased. To study whether the observed CP-induced MDSC expansion and activation also occurs under chronic inflammatory tumor-free conditions, mice exhibiting chronic inflammation were treated with CP. Similar to tumor-bearing mice, CP-treated inflamed mice displayed elevated levels of MDSCs with enhanced production of NO, reactive oxygen species, and a suppressed in vivo natural killer (NK) cell cytotoxic activity indicating CP effects on the host immune system independent of the tumor. We suggest that melanoma therapy with low-dose CP could be efficient only when combined with the neutralization of MDSC immunosuppressive function and chronic inflammatory microenvironment.